Poetic and theatrical occasionalisms: Creation of new morphologically complex words by Joseph von Eichendorff, Johann Nepomuk Nestroy, Peter Handke and Arno Schmidt - Dressler, Wolfgang U.; Tumfart, Barbara; Kunisch, Dietmar; Hannesschläger, Vanessa (Kalbotyra, 2024)
This contribution characterises and differentiates the poetic occasionalisms in the form of new morphologically complex words created by the early romantic German lyrical poet Joseph von Eichendorff, by the Austrian Nobel Prize winner for literature Peter Handke and by the extravagant German prosaic author Arno Schmidt and the occasionalisms created by the most famous Austrian comedy writer Johann Nepomuk Nestroy.The concept and term occasionalism has been founded by the Russian pioneer of stylistics Erik J. Chanpira (1996, see § 2) and defined as a newly created morphologically complex poetic word destined to be used with a literary function only once for a single passage and which is not taken over by anybody else. This definition holds for the authors investigated, except Eichendorff who reuses occasionalisms, which may be also reused by other lyrical poets of the same period or even later.The main part (§ 3) consists of the discussion of 17 criteria for characterising and differentiating the occasionalisms studied. These are productivity of word formation, literary functions, main content, single use vs. reuse of them, consequences of the noun bias of German and of the preference for binary relations, size of the word families of compound constituents (especially of the first constituent), the degree of poetic licence, semantically coherent vs. incoherent combination of words within a compound, embedding into the cotext and into the situational context, gapping constructions and their make-up, preference for compounding vs. derivational morphology.The conclusion and outlook (§ 4) present proposals how literary studies may profit from investigations of poetic and theatrical occasionalisms, which represent the highest degree of language creativity of literary authors. We urge that theatre productions should highlight occasionalisms and report that Nestroy’s German occasionalisms are generally better translated into English by programs of machine translation then by human translators.